THE EFFECT OF PROBLEM BASED LEARNING MODELS ON STUDENTS’ CRITICAL THINKING SKILL IN GEOGRAPHY CLASS XI IPS SMAN 1 PRINGSEWU - Maharani Maharani; Pargito Pargito; Listumbinang Halengkara (Journal Learning Geography, 2023)
This study aims to determine the effect of the problem based learning model on students' critical thinking skills in the geography subject of class XI IPS at SMA Negeri 1 Pringsewu. This study uses the correlational method. The population in this study were all students of class XI IPS SMA Negeri 1 Pringsewu with a research sample of class XI IPS 2 which was determined through simple random sampling technique. Data collection techniques in this study were carried out by tests, questionnaires and documentation. The data analysis technique used in this research is simple linear regression analysis to determine the effect of the problem based learning model on students' critical thinking skills in geography subjects. The results of the study show that the the problem based learning model has an effect on students' critical thinking skills in the geography subject of class XI IPS at SMA Negeri 1 Pringsewu with a significance value of 0.0030.05.